Unity, individuality and uniqueness of the person in the risk/benefit balance of the use of nutrigenetic tests in clinical practice - De la Garza, Ana Laura; Zonenszain-Laiter, Yael (Acta Bioethica, 2022)
In recent years, whole genome association studies have been conducted to identify genetic variants associated with the interindividuality of response to dietary treatments for weight loss. These nutritional genomics efforts contribute to the advancement of nutrition science 4.0: preventive, participatory, predictive and personalized. However, although to date more than 85 million polymorphisms have been discovered in the human genome, these findings do not indicate that the presence of these variations determines an effect on a personal health. Therefore, the use of the nutrigenetic profile for weight loss leads to analyze the risks/benefits with the bioethical principles focused on the unity, individuality and uniqueness of the human person. Thus, based on classical thinkers such as Aristotle and Thomas Aquinas, but with the contribution of contemporary philosophers, such as Robert Spaemman, the person is defined as an individual substance of a rational nature, breaking down the fundamental dimensions to demonstrate, by argumentation, that the principle individuality not only includes the biological dimension (materialistic naturalism), but the unity of the person belonging to human nature.